SOCIAL MEDIA, RELIGION AND RELIGIOSITY IN PAKISTAN IN THE ERA OF DISRUPTION - DR. TAHMINA RASHID (Hamdard Islamicus, 2021)
We are living in an era of disruption and the technological advancements have enabled us to manage work and family through remote access; replacing paper currency with cryptocurrency & phone wallets; and call centres with robot assistance. Technological disruptions are impacting social as well as spiritual relationships, leading to the emergence of virtual religious/spiritual communities, weakening the territorial divide. New technologies have also unsettled the status quo in these communities, as disruptive technologies* have enabled the emergence of new power centres, platforms and voices. Previously disempowered communities and groups are gaining agency using social media and effective use of global networks in the cyberspace. This paper explores the broader scene of disruptive technologies in relation to Muslims and Islam. It examines the social media landscape in Pakistan within the broader milieu of disruptive technologies. The research seeks to explores the impact of disruptive technologies on the society in Pakistan, examining the interplay of religion and religiosity in the era of disruptions, through four case studies selected from recent events in Pakistan. The article makes use of secondary resources to appraise the broader milieu of social media then, critically examines these case studies to know the impact of social media. These case studies highlight that social media is a powerful medium utilised by social activists as well as religious groups, a new phenomenon in the context of Pakistan.